DESINGING TASK-BASED INSTRUCTIONAL STRATEGY ON RECYCLING NEWSPAPER IN READING PROCEDURE TEXT - Atika, Sitti; ., Ikhsanudin; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research focuses on designing task-based instructional strategy on recycling newspaper to improve students’ in reading procedure text of SMAN 2 Sungai Raya Kabupaten Kubu Raya in Academic Year 2013/2014. The aim of this research is to construct teaching and learning strategy on recycling newspaper to improve students’ ability in reading procedure text for SMAN 2 Sungai Raya students. The research method used in this research is development research. The process in this research used analysis, design and development. The participants in this research are students and English teachers at SMAN 2 Sungai Raya. The researcher uses observation and interview as the tools of data collecting. Based on observation the researcher formulate the goals and learning objective. The interview findings the difficulties in teaching procedure text and effectiveness of the text book or LKS. Needs analysis obtains the following information about the goals, students’ experience, and identify the probable causes for a performance gap. The design phase explains relationship between approach and design be present a construct. The development phase represents activities and procedures planned for student’s activities. Keywords: Procedure Text, Newspaper, Development Research Abstrak: Penelitian ini berfokus pada merancang tugas berbasis perintah dengan menggunakan koran bekas untuk meningkatkan kemampuan siswa dalam membaca teks prosedure pada SMAN 2 Sungai Raya Kabupaten Kubu Raya tahun ajaran 2013/2014. Tujuan dari penelitian ini adalah untuk membangun gagasan strategi dalam belajar dan mengajar menggunakan koran bekas untuk meningkatkan kemampuan siswa dalam membaca teks prosedure pada siswa SMAN 2 Sungai Raya. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian pengembangan. Proses dalam penelitian ini menggunakan analisis, rancangan dan pengembangan. Penelitian ini berkaitan dengan siswa-siswa dan guru bahasa inggris di SMAN 2 Sungai Raya. Peneliti menggunakan pengamatan dan wawancara sebagai alat pengumpulan data. Berdasarkan pengamatan peneliti dapat merumuskan sasaran dan tujuan pembelajaran. Dalam wawancara menemukan kesulitan mengajar teks prosedure dan keefektipan buku atau lembar kerja siswa. Analisis terkait dengan informasi tentang sasaran, pengalaman siswa, dan masalah yang dihadapi. Tahap rancangan menjelaskan hubungan antara rancangan dan metode untuk menjadi gagasan. Pengembangan menjelaskan aktivitas-aktivitas dan tata cara merancang kegiatan siswa. Kata kunci: Teks prosedure, Koran, Penelitian Pengembangan